Proanthocyanidins against Oxidative Stress: From Molecular Mechanisms to Clinical Applications. (12th March 2018) - Yang, Lingyu; Xian, Dehai; Xiong, Xia; Lai, Rui; Song, Jing; Zhong, Jianqiao
Abstract : Proanthocyanidins (PCs) are naturally occurring polyphenolic compounds abundant in many vegetables, plant skins (rind/bark), seeds, flowers, fruits, and nuts. Numerous in vitro and in vivo studies have demonstrated myriad effects potentially beneficial to human health, such as antioxidation, anti-inflammation, immunomodulation, DNA repair, and antitumor activity. Accumulation of prooxidants such as reactive oxygen species (ROS) exceeding cellular antioxidant capacity results in oxidative stress (OS), which can damage macromolecules (DNA, lipids, and proteins), organelles (membranes and mitochondria), and whole tissues. OS is implicated in the pathogenesis and exacerbation of many cardiovascular, neurodegenerative, dermatological, and metabolic diseases, both through direct molecular damage and secondary activation of stress-associated signaling pathways. PCs are promising natural agents to safely prevent acute damage and control chronic diseases at relatively low cost. In this review, we summarize the molecules and signaling pathways involved in OS and the corresponding therapeutic mechanisms of PCs.